Technology of Developing Student Thinking Through Folk Crafts - Yuldashov Qaxramon Kamulovich (Genius Publishing Group, 2022)
The article emphasizes the importance of teaching schoolchildren the art of handicrafts, their spiritual upbringing, inculcation of national values in the universal form, the handicrafts of their people.
Keywords: student; education; upbringing; folk crafts